Task-specific effects of orientation information: neuropsychological evidence. - Cooper, A; Humphreys, G (2000)
The deficits underlying orientation agnosia in a patient (MB) with a right fronto-temporo-parietal lesion were examined. Like similar patients in the literature, MB was impaired at discriminating whether objects were upright or not and, in copying, she tended to re-represent stimuli as upright. In addition, MB failed to show the normal effects of rotation on object identification; her naming of objects rotated 45 degrees from upright was no slower than her naming of upright items. Effects of the degree of rotation did emerge, however, when she had to perform a matching task that required mental rotation. The evidence suggests that orientation may be coded in several ways (e.g. separately between objects and relative to the viewer), and that brain-damage can selectively affect the use of some but not all types of orientation information.